Investigating the icy crust and craters of Enceladus - Kroes, Thomas (author) (2019)
There has been a lot of research on Saturn’s moon Enceladus because of the plumes of water vapour emanating from this icy moon’s south pole. However, not much is known about the characteristics of the rest of the moon. This Thesis uses infrared spectral data gathered by Cassini’s VIMS instrument to search for traces of materials other than water ice and to characterize the crystal size and crystallinity of the water ice itself. The search for the non-water ice species was done by looking for features of the most likely candidates within the water ice spectra, while crystallinity and crystal size where evaluated based on several features of the water ice itself. This study has found traces of CO, CO2 and NH3, as well as an area of unusually high crystal size which might be indicative of a recent resurfacing event or previously unknown hot-spot. Aerospace Engineering